Influence of physical activity on myopic Brazilian adults: A pilot study - Dias de Jesus, Eduarda Eugenia; Rosa, Alexandre; Rodrigues, Luiz Henrique; Cortes Morales, Pedro Jorge (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to analyze the influence of physical activity on Brazilians with myopia. Sixty-three Brazilians with myopia participated. A questionnaire was used to identify the sample and the "Habitual Physical Activity Questionnaire" (HPAQ) was applied. In females, we found that the relationship of myopia with the night shift shows a moderate correlation (0.572) with a predominance of the right eye suggesting a higher incidence in this group. Sitting position at work shows a correlation as the inability to see at a distance, and this is a moderate correlation (0.585) for males. In view of this we see that there are other variables that can prevent the decrease of myopia, in which it is considerable to affirm that physical exercise alone is not enough for this population.